Powers of cycles, powers of paths, and distance graphs - Lin, M.C. (2011)
In 1988, Golumbic and Hammer characterized the powers of cycles, relating them to circular arc graphs. We extend their results and propose several further structural characterizations for both powers of cycles and powers of paths. The characterizations lead to linear-time recognition algorithms of these classes of graphs. Furthermore, as a generalization of powers of cycles, powers of paths, and even of the well-known circulant graphs, we consider distance graphs. While the colorings of these graphs have been intensively studied, the recognition problem has been so far neglected. We propose polynomial-time recognition algorithms for these graphs under additional restrictions. © 2010 Elsevier B.V. All rights reserved.